2017
DOI: 10.1080/2162402x.2017.1392426
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NK cell recognition of vemurafenib-treated melanoma cells is overcome by simultaneous application of histone deacetylase inhibitors

Abstract: Therapy of metastatic melanoma advanced recently with the clinical implementation of signalling pathway inhibitors, such as vemurafenib, specifically targeting mutant BRAF. In general, patients experience remarkable clinical responses under BRAF inhibitor (BRAFi) treatment but eventually progress within 6-8 months due to resistance development. Responding metastases show an increased immune cell infiltrate, including also NK cells, that, however, is no longer detectable in BRAFi-resistant lesions, suggesting N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 52 publications
7
64
0
Order By: Relevance
“…20 However, a direct inhibitory effect of PLX4032 on NK functions is unlikely, since BRAFis per se could not modify the NK cell phenotype, 4,36 and instead increased NK number were detected in peripheral blood, as shown in PLX4032-treated patients. In fact, an impaired cytotoxic activity of NK cells has been correlated to melanoma relapse and progression.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…20 However, a direct inhibitory effect of PLX4032 on NK functions is unlikely, since BRAFis per se could not modify the NK cell phenotype, 4,36 and instead increased NK number were detected in peripheral blood, as shown in PLX4032-treated patients. In fact, an impaired cytotoxic activity of NK cells has been correlated to melanoma relapse and progression.…”
Section: Discussionmentioning
confidence: 95%
“…In line with our results, it has been demonstrated that HO-1 is involved in the regulation of PD-L1 expression in renal cancer cells and its induction contributes to immuneescape. 20 They also showed that melanoma cell exposure to histone deacetylase inhibitors, known for their ability to increase the expression of ligands for NK activator receptors, 40 restored NK-mediated killing. It is conceivable that an important mediator of the immunomodulatory effect of HO-1 is CO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these results are in agreement with what other reports have shown for entinostat, vorinostat, and other HDAC inhibitors (sodium butyrate and sodium valproate) in other tumor types. 22,5154 One study found that hepatocellular carcinoma cells treated with sodium valproate had increased recognition by cytotoxic lymphocytes in an NKG2D-dependent manner, and increased the expression of MIC-A/B on these cells. 54 Another study reported that treatment of DAOY (medulloblastoma) and PC-3 cells with multiple HDAC inhibitors resulted in elevated expression of MIC-A/B, ULBP1-3, CD112, and CD155, and enhanced lysis of these cells by IL-2‒activated PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…22,5154 Our study simultaneously investigated tumor cell lines from NSCL, SCL, prostate, TNB, and ovarian origins, extending the effect of HDAC inhibition enhancing NK killing to novel tumor types. Additionally, our study provided a more comprehensive analysis of 12 different NK lysis relevant proteins on the surface of nine different cell lines encompassing five different tumor types (Tables 1 and 3, Supplemental Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%